TINJAUAN PERATURN TENTANG MASA JABATAN KEPALA DESA DENGAN PERATURAN-PERATURAN JABATAN KEPALA DAERAH: Review Of The Ruler On The Time Of The Village Head Office With The Regulations Of The District Head Office - Nurhayati Nurhayati (Yayasan Al-Amin Qalbu, 2025)
The term of office of village heads and regional heads is certainly different because both have their own regulations in the law, which is written about village regulations including Law Number 5 of 1979 concerning Village Government then replaced by Law No. 6 of 2014 concerning villages and after that changed to Law No. 3 of 2024 which regulates the term of office of village heads is 8 years and a maximum of 2 terms. Meanwhile, Article 162 Paragraph (1) and (2) of the same Law regulates that regional heads serve for five years. While Article 201 Paragraph (7) of Law Number 10 of 2016 concerning Regional Elections states that regional heads resulting from the 2020 Regional Elections serve until 2024. The research method used is a literature review or Library study. The purpose of this study is to analyze changes in the regulations on the term of office of village heads and regional heads. The results of the study show that there are many changes in the term of office of village heads and the term of office of regional heads which include several laws in them.